2016
DOI: 10.1016/j.cub.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

NIK/MAP3K14 Regulates Mitochondrial Dynamics and Trafficking to Promote Cell Invasion

Abstract: SUMMARY Although the role of NF-κB-inducing kinase (NIK) in immunity is well established, its relevance in cancer is just emerging. Here we describe novel functions for NIK in regulating mitochondrial dynamics and motility to promote cell invasion. We show that NIK is localized to mitochondria in cancer cell lines, ex vivo tumor tissue, and mouse embryonic fibroblasts (MEFs). NIK promotes mitochondrial fission, velocity, and directional migration, resulting in subcellular distribution of mitochondria to the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 64 publications
12
73
0
Order By: Relevance
“…Mechanistically, NF-κB-inducing kinase (NIK) seems to regulate DRP1 involvement in cell migration in multiple cancer types, including glioma, breast cancer, and pancreatic cancer (Jung et al, 2016). Loss of NIK greatly reduces invasive activity and causes congregation of mitochondria around the nucleus as opposed to their normal, predominantly anterograde movement toward the leading edge of migrating cancer cells.…”
Section: Cancer Cell Migrationmentioning
confidence: 99%
“…Mechanistically, NF-κB-inducing kinase (NIK) seems to regulate DRP1 involvement in cell migration in multiple cancer types, including glioma, breast cancer, and pancreatic cancer (Jung et al, 2016). Loss of NIK greatly reduces invasive activity and causes congregation of mitochondria around the nucleus as opposed to their normal, predominantly anterograde movement toward the leading edge of migrating cancer cells.…”
Section: Cancer Cell Migrationmentioning
confidence: 99%
“…Increased expression and activation of Drp1 in metastatic breast cancer cells results in smaller more motile mitochondria that, as evidenced by interfering with Drp1 function, promote the cell's metastatic potential (Zhao et al, ). NF‐κB‐inducing kinase has similarly been found to activate Drp1 and thereby promote mitochondria redistribution to the leading edges of migrating cancer cells (Jung et al, ). Invadopodia are protrusive structures used by migrating cancer cells to penetrate tissues and establish new sites of tumor growth (Seano and Primo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SNPH downregulation correlates also with poor survival prognosis in colon and lung adenocarcinoma patients [76]. Recently, it has been shown that NF-κB-inducing kinase (NIK) localizes at OMM in both MEFs and cancer cell lines where it interacts with Drp1, by promoting its translocation and activation; this favours fragmented mitochondria redistribution to lamellipodia and sustains high-speed cell migration [77]. Such a role is independent from the downstream mediators of NIK signalling [77].…”
Section: Mitochondrial Dynamics and Cell Migrationmentioning
confidence: 99%
“…Recently, it has been shown that NF-κB-inducing kinase (NIK) localizes at OMM in both MEFs and cancer cell lines where it interacts with Drp1, by promoting its translocation and activation; this favours fragmented mitochondria redistribution to lamellipodia and sustains high-speed cell migration [77]. Such a role is independent from the downstream mediators of NIK signalling [77]. Therefore, it seems that the metastatic potential of cancer cells often correlates with increased Drp1 or decreased Mfns activities, as shown -respectively, for breast cancer and glioma metastasis [71,74], and gastric cancer cells [71].…”
Section: Mitochondrial Dynamics and Cell Migrationmentioning
confidence: 99%